Proyecto de factibilidad para la implementación de una microempresa productora y comercializadora de pan integral en el cantón Zamora para el año 2015 - Jaramillo Delgado, Emérita Piedad (2016)
In this thesis project called " PROJECT FEASIBILITY FOR THE IMPLEMENTATION OF A SMALL BUSINESS PRODUCER AND DISTRIBUTOR OF PAN INTEGRAL IN ZAMORA CANTON FOR 2015 " , it aims to provide a study to satisfy the customer by offering a range of integrated products adapted to the reality of the population. Because of the need for a store that offers the inhabitants of the city of Zamora, a place to acquire healthy, great-tasting products, it is that the feasibility of implementing this project in response to these problems is analyzed. The purpose of creating this micro enterprise is to provide quality care to their customers, which will offer a service where each member will have a space just to purchase the products. During realization of this project, a general object called charted: To determine the commercial feasibility of implementing a producer and marketer of wholemeal bread company in the Zamora Canton 2015, which specific objectives which served as a guide raised to the study. In literature review it has been considered theoretical contents of different authors which served to know better the problem under study and specifically relates to the implementation of a company of integral bakery and service to be provided to the customer, including detailed concepts, classification, characteristics, processes, etc. To fulfill the objectives set methods, techniques and procedures that enabled research, develop and test the veracity of the project were used. The methods used were: Deductive method, it was used to meet demand with comprehensive baking products based on population. It was also used to analyze the supply allowing knowing that there are no companies dedicated to the development of comprehensive products in the canton Zamora. Inductive method was employed in the budgeting of costs because information split each of the costs of raw materials, supplies, materials and others to determine the production budget each year. The application of this method is based on the observation, ie seeing and hearing research-related phenomena. As for the techniques are applied: the observation that allowed us to know how it is carried out at present the process of production and marketing of wholemeal bread also was observed companies that exist in the sector and determine that there is no dedicated the development of integrated products, all the basic services are located. The research is based on primary information collected through surveys of shop owners, producers of bread and product claimants and secondary data provided by major public and private institutions. This project consists of the same five studies are: Market Research, Technical, Administrative, Economic, Financial and Environmental Assessment and Social Survey. Market research was conducted in the city of Zamora the same as applied to a representative sample of the population of the canton Zamora of 364 in habitants. In addition, the survey was applied to 40 vendors of wholemeal bread determining the following results: potential demand of 4,371 inhabitants, the actual demand of 2,797 inhabitants, and effective demand for 2,154 inhabitants. It was also estimated per capita consumption at 302 units therefore an expected demand of 650,508 units, associated with the offer that is 84,000.00 unmet demands is 566,533 units set is obtained. Technical study regarding the installed capacity of the plant to 376,320 units of whole grain bread set was developed. Like any production process cannot be started with 100% of its capacity due to several factors including market opening, selection of intermediaries engaging in the production process, personnel training, etc. Therefore it is planned to start with 80% of the installed capacity of the plant, that is, in the first and second year of operation of the company wholemeal 301,056 units will be produced. For the third and fourth year, will increase to 85% of production, ie 319,872, the fifth and sixth year, increased 90% to produce 338,688 units, the seventh and eighth to 95%, will produce 357,504 and last year. They work 100% ie 376.320 units produce wholemeal bread to be marketed in Zamora by the new company. Project engineering process diagrams determining the characteristics of operation and management, technical requirements such as equipment, facilities, furniture and fixtures were also developed. Likewise an administrative study determined the functional organizational structure hierarchical levels, such as operating manuals, organizational. In the study, an analysis of financial fixed assets, deferred assets and working capital to meet the project investment was made, the project reached 42,969.38 dollars an investment in which a loan with the Bank of Loja which corresponded to held 100 % 10-year period to 15.20 % monthly interest. The financial evaluation presents the following results: According to the NPV of this project gives us a positive value of $ 19,881.51, indicating that the investment project is appropriate, also the IRR is 22.51%, and this value satisfactory for the proposal in the administration. The Conclusions and Recommendations are set depending on the objectives set and achieved, therefore it was determined that the companies breadmaking available to the canton Zamora not meet the needs of customers, therefore and considering studies determined silver the project if feasible.